A comparative study of differences between participants in two popular sports - Mi, Jiayi; Qian, Zeyu (Cambridge Sport Science, 2025)
The article aims to explore the differences in leisure activity frequency between cyclists and runners, as well as the frequency of participation in various mass sports activities. It also analyzes the habits and experiences of participants in these two activities and explains the correlation between their participation in mass sports activities and their lifestyle. The study sample consists of leisure cyclists (194) and runners (664), including participants in two of China's largest mass sports events, the Lake Taihu International Cycling Race and the Beijing Marathon. The research is based on both quantitative and qualitative methods, and the results show that cyclists are more active than runners and participate in more activities. Moreover, the majority of those classified as "enthusiastic" participants are cyclists. The conclusion is that an individual's active lifestyle is influenced by their previous sports participation and experiences. Most of them consider engagement in sports as a way to evaluate themselves, and participation in different sports activities represents a unique leisure lifestyle.